Students' opinions of satisfaction and happiness in theclassroom: an evidence from a spanish virtual university - Cerdá Suárez, Luis Manuel; Valero Matas, Jesús Alberto (14th International Technology, Education and Development Conference (INTED2020), 2020)
From a comparative perspective, the analysis of the professors' attitudes and motivations in the classroom according to the students' opinions provides a relevant and interesting vision in order to facilitate this type of transformational teaching in the classroom. In particular, several authors have analyzed the relationship between satisfaction and happiness in the classroom grounded in empirical findings of Positive Psychology in face-to-face contexts, but studies are scarce on experiences in virtual universities. This paper aims: 1) to characterize a set of domains related to professors' behaviors providing positive emotions in the classroom; and 2) to assess their main dimensions for success from a Spanish virtual university. Firstly, this manuscript describes a review of this emotional approach in learning and teaching and secondly, a rigorous managerial process in the classroom is validated. Additionally, we applied several in-depth interviews and a questionnaire to a diverse sample of students evaluating the behavior of their professors in the classroom. Our results and conclusions reinforce the importance to implement experiential academic projects in virtual universities and promote happiness and satisfaction to different levels of management in the classroom.
Keywords: teaching; happiness; classroom; higher education; virtual university; WOS(2)